Plasma levels of plasminogen activator inhibitor‐1 and bleeding phenotype in patients with von Willebrand disease. Issue 3 (17th March 2017) - Abdul, S.; Boender, J.; Malfliet, J. J. M. C.; Eikenboom, J.; Fijn van Draat, K.; Mauser Bunschoten, E. P.; Meijer, K.; de Meris, J.; Laros‐van Gorkom, B. A. P.; van der Bom, J. G.; Leebeek, F. W. G.; Rijken, D. C.; et al.
Abstract : Introduction: von Willebrand disease (VWD) is the most common inherited bleeding disorder. In VWD patients, large variations in bleeding tendency are observed, which cannot be completely explained by the variation in von Willebrand factor levels or activities. Thus, there must be additional factors, for instance, changes in fibrinolysis that have an effect on the variation in bleeding tendency in VWD patients. Aim: To investigate whether plasminogen activator inhibitor‐1 (PAI‐1) level influences the variation in bleeding tendency in VWD patients. Methods: PAI‐1 antigen levels were measured in the plasma of 633 patients with moderate or severe VWD who participated in the 'Willebrand in the Netherlands' (WiN) study, a nationwide multicentre cross‐sectional study. Bleeding severity was assessed using the Tosetto bleeding score. Results: PAI‐1 levels increased with age (Spearman's rho: 0.225, P < 0.001) and were higher in men (23 [IQR 12–60] vs. 20 [IQR 10–44] ng mL −1 in women, P = 0.039), whereas the bleeding score was higher in women (11 [IQR 7–17] vs. 9 [IQR 5–14] ng mL −1 in men, P = 0.002). After adjustment for age and sex by stratification, PAI‐1 level and bleeding score were negatively correlated (Spearman's rho: −0.170, P = 0.017) in the group of 196 young (age ≤ 45 year) female VWD patients, accounting for 31% of our study population. Conclusion: In young female VWD patients, we observed that low PAI‐1 levels were associated with a higher bleeding score, which may partly explain the observed variability in bleeding phenotype in VWD patients.